Global production networks : operations design and management - Errasti, Ander (CRC Press, 2013)
The phenomenon of globalization has increased in recent decades due to the opening of borders in Eastern Europe and the sudden emergence of other countries in the global trade economy. Yet, the process of becoming global to get access to growing markets or to achieve quality, service, and/or cost advantages from the reconfigured Value Chains is one of the most complex processes that companies undertake. Global Production Networks: Operations Design and Management addresses the challenges that companies face and proposes a range of innovative methodological approaches when designing and impleme.